Histopathological Patterns of Endometrial Biopsies in Abnormal Uterine Bleeding with Special Reference to Endometrial Carcinoma: A Study from North East India - Kaur, Daljeet; Devi, Junu; Brahma, Valina; Kanya, Nani (Annals of Pathology and Laboratory Medicine, 2024)
Background: Abnormal uterine bleeding (AUB) is the most commonly presented gynecological symptom in women of all age groups. Endometrial sampling followed by its histopathological examination is an indispensable tool to investigate the cause of AUB. Materials and Methods: The study was a hospital-based cross-sectional study that included 272 endometrial biopsies sent to the Pathology department for histopathological examination. The duration of the study was one year. Only endometrial biopsies for non-gestational AUB were included in the study. After processing the formalin-fixed tissue, paraffin blocks were made. Four-micron thick slides were prepared, stained with Hematoxylin & Eosin stain, and thoroughly examined under scanner, low, and high-power view. The samples were categorized by age groups and clinical presentation of uterine bleeding. The study was approved by the Institutional Ethics Committee. Results: Out of 272 endometrial biopsies, 254 biopsies could be evaluated, as 18 were non-diagnostic due to cellular inadequacy. The majority of the patients (42.1%) were in the 41–50 years age group. Normal cyclical changes (35.8%) constituted the most common histopathological findings, followed by disordered proliferative endometrium (27.9%). Malignant lesions were detected in 1.2% of cases, while endometrial hyperplasia constituted 26.4% of cases, emphasizing the importance of endometrial biopsies in detecting precursor lesions and treating them in their early pre-invasive stages, thereby reducing morbidity and mortality (p-value 0.0001). Conclusion: Endometrial sampling should be considered in all cases presenting with AUB. Histopathological examination of the endometrium should be regarded as the first-line investigative modality in peri- and post-menopausal age groups, where the incidence of endometrial hyperplasia and endometrial carcinoma is higher.